Natural Daylighting Performance at Stilt House in Jambi City - Pratomo Soni (Tamkang University Press, 2021)
The stilt house in Seberang Jambi City is a heritage of Jambi Malay culture. There is something unique on the sheath of this stilt house. The window section has various sizes, for example, the window size on the living room is larger than the family room. The application of these window apertures depends on the function of space in the house. This research is preliminary research regarding the architectural aspects of the stilt house. The purpose of this research is to find out the performance of natural daylighting on the stilt house by considering the aspect ratio of the window area, like dimensions, the shape, and position of the window. The method of this research is a field survey as quantitative descriptive analysis. Simulation Method of DIALux 4.2 used for data validation and evaluation of natural daylighting performance. The result of this research is expected to strengthen the study of cultural heritage concepts in Seberang Jambi City. Through the study of the application of aperture on the building sheath in the stilt house in Seberang Jambi City has a good natural daylighting performance to fulfill the standard of visual comfort for the activity. This can be seen from the preliminary research data shows on stilt houses have a daylighting intensity value of 200 - 800 lux in the living room and family room at 12.00 pm.